Neural Progenitors in the Developing Neocortex of the Northern Tree Shrew (Tupaia belangeri) Show a Closer Relationship to Gyrencephalic Primates Than to Lissencephalic Rodents - Römer, Sebastian; Bender, Hannah; Knabe, Wolfgang; Zimmermann, Elke; Rübsamen, Rudolf; Seeger, Johannes; Fietz, Simone A. (Frontiers in Neuroanatomy, 2018)
The neocortex is the most complex part of the mammalian brain and as such it has undergone tremendous expansion during evolution, especially in primates. The majority of neocortical neurons originate from distinct neural stem and progenitor cells (NPCs) located in the ventricular and subventricular zone (SVZ). Previous studies revealed that the SVZ thickness as well as the abundance and distribution of NPCs, especially that of basal radial glia (bRG), differ markedly between the lissencephalic rodent and gyrencephalic primate neocortex. The northern tree shrew (Tupaia belangeri) is a rat-sized mammal with a high brain to body mass ratio, which stands phylogenetically mid-way between rodents and primates. Our study provides – for the first time – detailed data on the presence, abundance and distribution of bRG and other distinct NPCs in the developing neocortex of the northern tree shrew (Tupaia belangeri). We show that the developing tree shrew neocortex is characterized by an expanded SVZ, a high abundance of Pax6+ NPCs in the SVZ, and a relatively high percentage of bRG at peak of upper-layer neurogenesis. We further demonstrate that key features of tree shrew neocortex development, e.g. the presence, abundance and distribution of distinct NPCs, are closer related to those of gyrencephalic primates than to those of ferret and lissencephalic rodents. Together, our study provides novel insight into the evolution of bRG and other distinct NPCs in the neocortex development of Euarchontoglires and introduces the tree shrew as a potential novel model organism in the area of human brain development and developmental disorders.